Profiling the disciplinary foundation of telework research: A journal co-citation analysis - Vásquez, Anibal Pinchi; Larrañaga, Katty Álamo; Sánchez, Teresa del Pilar Lopez; Trigoso-García, Carlos; Vela, Jerris Rojas; Rengifo-Amasifen, Roger Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. This study employed bibliometric analysis to identify the most relevant journals in telework research and utilized journal co-citation analysis to map the intellectual foundation of this field of study. Design/Methodology/Approach. To conduct this study, we used data from Scopus, employed the cluster modularity technique to identify journal communities, gathered centrality measures to pinpoint essential journals, and chose to rank the journals based on relevance. We combined two key measures to achieve this: the number of citations received and closeness centrality within the co-citation network. Results/Discussion. Seven communities of journals were identified, encompassing the following subject areas: organizational psychology and management, technology and information systems, occupational health and psychological well-being, sustainability and the environment, education and skills development, economics and public policy, and sociology and cultural studies. Some of the most relevant journals included the Journal of Applied Psychology; the International Journal of Environmental Research and Public Health; Sustainability, the Journal of Organizational Behavior; the Journal of Vocational Behavior; New Technology, Work and Employment; Frontiers in Psychology; Human Relations; the Academy of Management Journal; and the Academy of Management Review. Conclusions. The co-citation analysis revealed that the disciplinary structure of teleworking is underpinned by a network of influential journals covering different areas of knowledge. The most relevant publications form seven major thematic clusters, reflecting the multidisciplinary nature of teleworking research.